(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
A good knowledge of disease management is necessary in promoting care and enhancing good therapeutic outcomes. The present study analyzed the knowledge, attitude and practice of hospital pharmacists in three referral hospitals to assess their preparedness in rendering pharmaceutical care to type 2 diabetic outpatients according to current pharmacy practices. The study was a cross-sectional survey of randomly selected hospital pharmacists at three teaching hospitals in eastern Nigeria. Retrospective data was collected using a structured questionnaire and analyzed based on descriptive statistics. A total of 130 hospital pharmacists comprising of 81 (62.3%) males and 49 (37.7%) females participated in the study. The mean duration of number of years of practice for the respondents was 23.3, 16.7 and 5.1 for University of Nigeria Teaching Hospital, Nnamdi Azikiwe University Teaching Hospital and Enugu State University Teaching Hospital, respectively. The survey revealed that the pharmacists had good knowledge of the diabetes disease and its management. While 83% believed that diabetes is dangerous, 17% felt that it should not be considered as a dangerous disease. Some of the pharmacists (25%) were of the view that patients’ education is not the most important management tool in diabetic care while 10.8% felt that diabetic patients do not need special attention.